2019
DOI: 10.1080/21681805.2019.1575467
|View full text |Cite
|
Sign up to set email alerts
|

Is Bcl-2 a predictive marker of neoadjuvant chemotherapy response in patients with urothelial bladder cancer undergoing radical cystectomy?

Abstract: Background: Response to neoadjuvant cisplatin treatment in bladder cancer has been linked to expression of Bcl-2 protein by cancer cells. The objective of this study was to test Bcl-2 as a predictive marker of neoadjuvant cisplatin chemotherapy response in a patient cohort from randomized cystectomy trials. Methods: Tumor samples were taken from 247 patients with T2-T4 bladder cancer enrolled in two randomized trials comparing cystectomy with or without neoadjuvant chemotherapy. Tissue microarrays from pre-int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
(41 reference statements)
1
1
0
Order By: Relevance
“…Our study showed that no significant difference was found in pre-NACT Bcl-2 expression among different NACT efficacy. The earlier clinical study conducted among 247 bladder cancer patients with NACT reported similar findings to ours [ 8 ]. With regard to cervical cancer, Harima et al [ 34 ] also presented that the Bcl-2 expression prior to radiotherapy did not correlate with treatment response.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study showed that no significant difference was found in pre-NACT Bcl-2 expression among different NACT efficacy. The earlier clinical study conducted among 247 bladder cancer patients with NACT reported similar findings to ours [ 8 ]. With regard to cervical cancer, Harima et al [ 34 ] also presented that the Bcl-2 expression prior to radiotherapy did not correlate with treatment response.…”
Section: Discussionsupporting
confidence: 90%
“…Bcl-2 plays an important role in the intrinsic apoptotic pathway of malignant cancer and has been shown to interfere with chemotherapy [ 7 ]. Preferentially, the expression of CD34 and Bcl-2 were proved to be the predictors of neoadjuvant chemotherapy in urothelial bladder cancer [ 8 ] and breast cancer [ 9 , 10 ]. However, up until now, less study has been dedicated to clarify the association between CD34 or Bcl-2 expression and the response to NACT in cervical cancer.…”
Section: Introductionmentioning
confidence: 99%